Information Technology in Biomedicine Proceedings 6th International Conference, ITIB'2018, Kamień Śląski, Poland, June 18-20, 2018 - Pietka, Ewa.; Badura, Pawel; Kawa, Jacek; Wieclawek, Wojciech; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
ITiB'2018 is the 6th Conference on Information Technology in Biomedicine, hosted every two years by the Department of Informatics & Medical Devices, Faculty of Biomedical Engineering, Silesian University of Technology. The Conference is organized under the auspices of the Committee on Biocybernetics and Biomedical Engineering of the Polish Academy of Sciences. The meeting has become an established event that helps to address the demand for fast and reliable technologies capable of processing data and delivering results in a user-friendly, timely and mobile manner. Many of these areas are recognized as research and development frontiers in employing new technology in the clinical setting. Technological assistance can be found in prevention, diagnosis, treatment, and rehabilitation alike. Homecare support for any type of disability may improve standard of living and make people's lives safer and more comfortable. The book includes the following sections: Ø Image Processing Ø Multimodal Imaging and Computer-aided Surgery Ø Computer-aided Diagnosis Ø Signal Processing and Medical Devices Ø Bioinformatics Ø Modelling & Simulation Ø Analytics in Action on the SAS Platform Ø Assistive Technologies and Affective Computing (ATAC) .
Keywords: Computational intelligence; Biomedical engineering; Medical informatics; Artificial intelligence; Computational Intelligence; Biomedical Engineering and Bioengineering; Health Informatics; Artificial Intelligence